WORKING GROUP ON DRY GRASSLANDS IN THE NORDIC AND BALTIC REGION - OUTLINE OF THE PROJECT AND FIRST RESULTS FOR THE CLASS FESTUCO-BROMETEA - DENGLER, JURGEN; RUSINA, SOLVITA; BOCH, STEFFEN; BRUUN, HANS HENRIK; DIEKMANN, MARTIN; DIERSSEN, KLAUS; DOLNIK, CHRISTIAN; DUPRE', CECILIA; GOLLUB, VALENTIN B.; GRYTNES, JOHN-ARVID; HELM, AVELLINA; INGERPUU, NELE; et al. (Annali di Botanica, 2006)
The vegetation databank established by our working group covers the classes FestucoBrametea. Koelerio-Corynephoretea, and Trifolio-Geranietea sanguinei in the Nordic and Baltic region. i.e. NE Germany, Denmark, Norway, Sweden, Finland. N Poland. Lithuania, Latvia, Estonia. and NW Russia. We aim to use these data to develop a consistent supra-national phy~ tosociological classification of these xerothermic vegetation types in the study area and to analyse their biodiversity patterns. Up to now, we located some 12,500 releves meeting our criteria, and more than 3.500 of them have already been included in the databank. We give an overview of the properties of these releves as regards coverage of syntaxa and countries, source types, plot sizes, and cryptogam treatment. We also present first analyses for the basiphilous semi·dry grasslands (Brachypodietalia pinnati) within the Festuco-Brometea. For this group of communities, many different and incompatible classification schemes have been proposed. We givc an overview of the alliance and aSsociation names that have been in use for them in the study area, accompanied by a nomenclatural assessment. The releves presently included in the databank havc been tentatively assigned to those vegetation classes whose diagnostic taxa were prevailing. Accordingly, morc than 2.000 releves have been placed in the Festuco-Brometea. These show considerable floristic differenccs compared to stands of the southern temperate Brachypodietalia pinnati alliances Bromion erecti, Cirsio-Brachypodion pinnati, and Agrostionvinealis. The presence degrees of Avenula pratensis and Homalothecium lutescens, for instance, are significantly increased in the study area, and those of Festuca rupieola and Euphorbia cyparissias decreased. An analysis of the species-area relationship yielded a power function with z = 0.09 which is considerably lower than increments determined by nested-plot analyses of this community type, indicating the probable incompleteness of the species lists for many of the larger plots. Finally, we give an outlook on the future objectives of the working group.